Users May Lack Confidence in ART for HIV Prevention: A Qualitative Analysis - Wyatt, Monique A.; Pisarski, Emily E.; Baeten, Jared M.; Heffron, Renee; Nakku-Joloba, Edith; Muwonge, Timothy R.; Katabira, Elly T.; Celum, Connie L.; Ware, Norma C. (Conference on retroviruses and opportunistic infections (CROI), 2017)
Antiretroviral-based approaches to HIV prevention have been shown to reduce new infections in clinical trials and demonstration settings. To optimize uptake and anticipate barriers to effective rollout, we must understand users’ perspectives on antiretroviral treatment (ART) for prevention of HIV transmission. We explored serodiscordant couples’ understandings of and feelings about treatment as prevention using qualitative data from the Partners Demonstration Project. The Partners Demonstration Project employed an integrated delivery strategy of daily oral pre-exposure prophylaxis (PrEP) and ART for serodiscordant couples in Kenya and Uganda. PrEP use was time-limited and discontinued after HIVinfected partners had been on ART for 6 months. Multiple in-depth qualitative interviews were conducted with a subset of 48 couples from the Kampala, Uganda Partners Demonstration Project site (N interviews=195). Interview topics included: (a) perceived purpose and meanings of PrEP and ART; (b) adherence; (c) experiences of PrEP discontinuation; and (d) understandings of antiretroviral treatment as prevention. Interviews were audio-recorded, transcribed into English and coded using Atlas.ti software by two trained analysts. Coded data were inductively analyzed to identify themes representing couples’ understandings of and feelings about using ART for prevention of HIV transmission. Categories were developed to represent the themes.